2023
DOI: 10.1007/s10238-023-01038-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of ACE1, ACE2, IFTM3, TMPRSS2 and TNFα genes associated with susceptibility and severity of SARS-CoV-2 infection: a systematic review and meta-analysis

Abstract: Background Some human polymorphisms of ACE1, ACE2, IFITM3, TMPRSS2 and TNFα genes may have an effect on the susceptibility to SARS-CoV-2 infection and increase the risk to develop severe COVID-19. We conducted a systematic review of current evidence to investigate the association of genetic variants of these genes with the susceptibility to virus infection and patient prognosis. Methods We systematically searched Medline, Embase and The Cochrane Library for articles published until May 2022, and included obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Accompanying the spread of COVID-19 disease all over the world, recognizing factors connected to the susceptibility and outcome of the disease is at the top of medical and pharmacological concerns [ 23 ]. This work was performed to identify possible COVID-19 prognostic markers with special concern for ACE-2 and IFITM-3 genetic variations and IL-6 level assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying the spread of COVID-19 disease all over the world, recognizing factors connected to the susceptibility and outcome of the disease is at the top of medical and pharmacological concerns [ 23 ]. This work was performed to identify possible COVID-19 prognostic markers with special concern for ACE-2 and IFITM-3 genetic variations and IL-6 level assays.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analytic study involving more than four studies from England, Italy, and Spain showed a significant association of the IFITM-3 rs12252/ ACE-2 rs2285666 polymorphism with COVID-19 susceptibility [ 43 ]. However, neither rs2285666 nor rs12252 were shown to be substantially related to illness severity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 acts as a receptor and serves as a possible route by which the coronavirus can enter cells, while TMPRSS2 is a membrane proteinase that can aid the virus in entering cells. The ACE2 protein is the cause of the lung infection triggered by SARS-CoV-2; it is mainly expressed on the surfaces of the human respiratory tract and lung cells [ 3 ]. When the virus enters the host cells, TMPRSS2 cuts the virus membrane protein, promoting its replication and infection, and it is mainly located on the surfaces of human respiratory tract cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review and meta-analysis revealed that genetic variants within the angiotensin-converting enzyme 1 and 2 genes (ACE and ACE2, respectively) and the transmembrane serine protease 2 (TMPRSS2) gene were associated with COVID-19 severity [28]. Moreover, a systematic review found that ACE and the interferon-induced transmembrane protein 3 (IFTM3) gene polymorphisms may lead to a genetic predisposition for severe lung injury in COVID-19 patients [29]. Also, genome-wide association study (GWAS) metaanalyses of the COVID-19 Host Genetics Initiative identified 14 loci associated with COVID-19 disease severity or hospitalization [30].…”
Section: Introductionmentioning
confidence: 99%